Pregabalin for Postoperative pain in patients undergoing spinal surgery: A Dose ranging randomized clinical study - Goel, Palak; Kotia, Anshu S.S.; Kumar, Anil; Bana, Mona; Meena, Reena; Singh, Tarun (Pain medicine, 2023)
Background: The efficacy of pregabalin in acute post-surgical pain management is well demonstrated. As, the use of pregabalin is officially not approved and hence, there is no dosing guideline as well. Aim: To determine whether single preoperative administration of different doses of pregabalin (150 mg to 300mg) could decrease postoperative pain intensity following spinal surgery. Materials and Method: In this prospective, randomized double-blinded study, a total 60 patients undergoing spinal surgery were selected and randomly assigned any of these four groups of 15 each; group A (received placebo drug), group B (received pregabalin 150mg), group C (received pregabalin 200mg) and group D (received pregabalin 300mg). All the groups received the said drugs (coded as it was double-blinded study) in the same manner and two hours prior to operation. The patients were followed for pain scores on visual analogue scale (VAS), time to rescue analgesia and side effects as secondary outcomes. Results: Patients in pregabalin dose ranging group had lower pain in the initial hour of recovery. However, the pain scores subsequently decreased and became similar in all groups. Time for the requirement for analgesic was longer in pregabalin 300mg group when compared with other study groups. Conclusion: A single dose of 300 mg pregabalin given 1–2 hours prior to surgery is superior to placebo after spinal surgery.